3d Printing Applications in Creative Advertising Marketing: A Review - Ali, Nashwa; Elnaggar, Khaled (International Journal of Membrane Science and Technology, 2023)
3D printing as digital manufacturing is considered the multiple aspects of the industry field, especially in advertising. This type of knowledge is based on the concept of a multi-layer fabrication technique called additive manufacturing, which produces physical objects created in 3D software (e.g., Maxon C4D, Autodesk Fusion 360, AutoCAD, Autodesk Maya, etc.) and then transforms the dimensional object to (e.g., G-Code). This article focuses on a question: Is there the importance of 3D printing application techniques, materials, and manufacturing in the field of advertising as a creative tool that can bring atypical formulation in advertising designs and create a new marketplace? They play an active part in promoting the product due to the absence of studies that focus on the presence of 3D printing in the advertising business, especially outdoor ones such as road advertisements or multidimensional wall advertisements. the findings from this study suggest that 3d applications like 3d advertising manufacturing, special materials, or other intelligent fabrication may be influenced by its method and process to a moderate degree as a new marketplace and strategy.